Attitudes of teachers and students’ guardians towards the application of the "Trimester" in The Kingdom of Saudi Arabia - Al-Shammari, Najwa Mohammed Abdallah (Journal of Curriculum and Teaching Methodology, 2023)
The study aims at identifying the teachers’ and parents’ attitudes towards implementing the T- Semester in the Kingdom of Saudi Arabia. It also aims at determining the solutions and developmental suggestions from the teachers’ and parents’ perspective. The descriptive analytical approach was used in this study, and it was conducted on a random sample of (114) teachers from Makkh Al- Mokarama schools. It also conducted on (123) parents. The total number of the sample was (237). The tool of the study consisted of two questionnaires. The results of the study indicated that the teachers’ and parents’ attitudes were low in the negative attitude towards the system’s advantages domain, while their attitudes were high in the positive attitude towards the disadvantages domain of the system. The study also indicated that the majority of the teachers (72% of them) proposed eliminating three- semester system, whereas 5% of them suggested it was somewhat appropriate and it did not need any elimination or development. 5% of them suggested maintaining T- Semester, but it needs overall development, including its curricula, school day hours, implementation mechanism, the number of days off and duration. 5% of teachers suggested that the system needs only to be developed in a way that suits the curricula with the number of semesters, while 3% of teachers suggested maintaining the system by reducing the number of school day hours. On the other hand, the majority of the parents (85% of them) proposed eliminating T- semester, , whereas 5% of them suggested that the system needs only to be developed in a way that suits the curricula with the number of semesters. 2% of parents suggested preserving the system, but reducing the school day hours. 2% see the necessity of keeping three- semester system and developing it in general to suit the needs of teachers and students. The results also indicated that there were no statistically significant differences among the means of teachers’ responses regarding to the gender, experience, educational stage variables and there was a significant difference in the negative domain in favor of postgraduate and baccalaureate qualifications. There were also no statistically significant differences among the means of parents’ responses towards implementing T-semester according to the gender and qualification variables.